2022
DOI: 10.3389/fpsyt.2022.938275
|View full text |Cite
|
Sign up to set email alerts
|

Distress-driven impulsivity interacts with trait compulsivity in association with problematic drinking: A two-sample study

Abstract: ObjectiveProblematic drinking is highly prevalent among the general population, oftentimes leading to significant negative consequences, including physical injury, psychological problems and financial hardship. In order to design targeted early interventions for problematic drinking, it is important to understand the mechanisms that render individuals at risk for and/or maintain this behavior. Two candidate drivers of problematic drinking are distress-driven impulsivity and trait compulsivity, with recent rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…By pinpointing specific pathways that link the Big Five personality traits to PSU, our results support prior theoretical assumptions on mechanisms underlying PSU. Specifically, it has been proposed that the excessive reassurance pathway linking Neuroticism and PSU is relevant to negative reinforcement i.e., individuals engage in smartphone use as a coping strategy to address negative emotions ( Elhai et al., 2017 ; Pivetta et al., 2019 ), a well-documented mechanism underlying addictive behaviours ( Baker, Piper, McCarthy, Majeskie, & Fiore, 2004 ; Liu et al., 2021 ; Liu, Rotaru, Chamberlain, Ren, et al., 2022 ; Liu, Rotaru, Chamberlain, Yücel, et al., 2022 ). In line with this view, numerous studies reported positive associations between Neuroticism and overall PSU ( Gao et al., 2020 ; Marengo et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…By pinpointing specific pathways that link the Big Five personality traits to PSU, our results support prior theoretical assumptions on mechanisms underlying PSU. Specifically, it has been proposed that the excessive reassurance pathway linking Neuroticism and PSU is relevant to negative reinforcement i.e., individuals engage in smartphone use as a coping strategy to address negative emotions ( Elhai et al., 2017 ; Pivetta et al., 2019 ), a well-documented mechanism underlying addictive behaviours ( Baker, Piper, McCarthy, Majeskie, & Fiore, 2004 ; Liu et al., 2021 ; Liu, Rotaru, Chamberlain, Ren, et al., 2022 ; Liu, Rotaru, Chamberlain, Yücel, et al., 2022 ). In line with this view, numerous studies reported positive associations between Neuroticism and overall PSU ( Gao et al., 2020 ; Marengo et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, groups have emphasized the fundamental role of conflict for compulsive aspects of addiction (19, 22, 58) (discussed in Section 2), as well as high motivation, reflected in https://pubs.niaaa.nih.gov/publications/surveillance /figures .htm# f part by continuation of responding despite the cost of dealing with negative consequences (3,27). Other aspects of compulsion, including considerations and caveats, are discussed in several recent reviews (59)(60)(61)(62)(63), and we predominantly agree with the points they detail in our publications (64)(65)(66)(67)(68)(69)(70). These include (1) considerations of overfocus on compulsion, to the detriment of overlooking other factors that can contribute to addiction (59-61, 65, 71) (above), (2) the importance of considering compulsion for alcohol when adapting the NIMH RDoC framework for addiction (3,72,73), and (3) the importance of agency and knowledge of choosing during recovery from compulsion-like drinking pattern (19,20,74,75).…”
mentioning
confidence: 99%
“…This inability to shift attention away from previously rewarding cues, paired with high relief-based motives, may predict harmful drinking through persistence of maladaptive coping strategies despite its negative consequences ( Cox and Klinger, 1988 , Wiers et al, 2007 ). Our team recently found this effect at the trait-level, using a trait compulsivity self-report questionnaire to reflect cognitive inflexibility, across two independent samples of people who consume alcohol ( Albertella et al, 2020 , Liu et al, 2022 , Liu et al, 2022 ). Specifically, we found that trait compulsivity moderated the association between distress-driven impulsivity and problematic drinking in university students and a general community sample ( Liu et al, 2022 , Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 97%
“…Our team recently found this effect at the trait-level, using a trait compulsivity self-report questionnaire to reflect cognitive inflexibility, across two independent samples of people who consume alcohol ( Albertella et al, 2020 , Liu et al, 2022 , Liu et al, 2022 ). Specifically, we found that trait compulsivity moderated the association between distress-driven impulsivity and problematic drinking in university students and a general community sample ( Liu et al, 2022 , Liu et al, 2022 ). It is important, however, to determine whether this effect can be observed at the objective cognitive level, via cognitive flexibility tasks, and in more population-representative samples, which to our knowledge, has not been evaluated in alcohol use, thus far.…”
Section: Introductionmentioning
confidence: 97%